Transport, Fate and Impacts of the Deep Plume of Petroleum Hydrocarbons Formed During the Macondo Blowout - Bracco, Annalisa; Paris, Claire B.; Esbaugh, Andrew J.; Frasier, Kaitlin; Joye, Samantha B.; Liu, Guangpeng; Polzin, Kurt L.; Vaz, Ana Carolina (Frontiers in Marine Science, 2020)
The 2010 Macondo oil well blowout consisted in a particularly intense, localized infusion of petroleum hydrocarbons to the deepwaters of the Gulf of Mexico. A substantial amount of these hydrocarbons did not reach the ocean surface but remained confined at depth within an intrusion layer at about 1000 m of depth. This layer, or plume, impacted the Gulf's benthic, mesopelagic and pelagic ecosystems, damaging also fish and mammals. This review outlines the challenges the science community overcame since 2010, the discoveries and the remaining open questions in interpreting and predicting the distribution, fate and impact of the Macondo oil in the deepwater plume. In the past ten years, the scientific community supported by, among others, the Gulf of Mexico Research Initiative, has achieved key milestones in observing, conceptualizing and understanding the physical oceanography of the Gulf of Mexico, not only at the surface but also along its northern continental shelf and slope. Major progress has been made also in modeling the transport, evolution and degradation of hydrocarbons. Here we review this new knowledge and modelling tools, how our understanding of the deep plume has evolved, and how research in the past decade may help preparing in the event of a future spill in the Gulf or elsewhere. Observational, theoretical, and modelling limitations, however, still constrain our ability to predict the three-dimensional movement of water in this basin, and the fate and impacts of the hydrocarbons they may carry.